Childhood Exposure to Passive Smoking and Bone Health in Adulthood: The Cardiovascular Risk in Young Finns Study - Markus Juonala; Niina Pitkänen; Sanna Tolonen; Marika Laaksonen; Harri Sievänen; Eero Jokinen; Tomi Laitinen; Matthew A Sabin; Nina Hutri-Kähönen; Terho Lehtimäki; Leena Taittonen; Antti Jula; et al. (ENDOCRINE SOC, 2022)
Context: Passive smoke exposure has been linked to the risk of osteoporosis in adults.
Objective: We examined the independent effects of childhood passive smoke exposure on adult bone health.
Design/Setting: Longitudinal, the Cardiovascular Risk in Young Finns Study.
Participants: The study cohort included 1422 individuals followed for 28 years since baseline in 1980 (age 3 to 18 years). Exposure to passive smoking was determined in childhood. In adulthood, peripheral bone traits were assessed with peripheral quantitative CT (pQCT) at the tibia and radius, and calcaneal mineral density was estimated with quantitative ultrasound. Fracture data were gathered by questionnaires.
Results: Parental smoking in childhood was associated with lower pQCT-derived bone sum index in adulthood (beta +/- SE, -0.064 +/- 0.023 per smoking parent; P= 0.004) in multivariate models adjusted for age, sex, active smoking, body mass index, serum 25-OH vitamin D concentration, physical activity, and parental socioeconomic position. Similarly, parental smoking was associated with lower heel ultrasound estimated bone mineral density in adulthood (beta +/- SE, -0.097 +/- 0.041 per smoking parent; P = 0.02). Parental smoking was also associated with the incidence of low-energy fractures (OR, 1.28; 95% CI, 1.01 to 1.62). Individuals with elevated cotinine levels (3 to 20 ng/mL) in childhood had lower bone sum index with pQCT (beta +/- SE, -0.206 +/- 0.057; P = 0.0003). Children whose parents smoked and had high cotinine levels (3 to 20 ng/mL) had significantly lower pQCT-derived bone sum index compared with those with smoking parents but had low cotinine levels (<3 ng/mL) (beta +/- SE, -0.192 +/- 0.072; P = 0.008).
Conclusions and Relevance: Children of parents who smoke have evidence of impaired bone health in adulthood.